Rango de Hogar y uso de Hábitat de Carpinchos en Pastizales recién invadido en el Chaco Seco de Paraguay - Campos-Krauer, Juan M.; Wisely, Samantha M.; Benitez, Ivan K.; Robles, Victor; Golightly, Richard T. (THERYA, 2014)
Introduction: Deforestation is one of the primary causes of species decline worldwide. Some species, however, can take advantage of change and expand their distribution, putting endemic species in danger of extinction, changing the composition of biotic communities, and altering ecosystems. Methods: From June 2005 to July 2007, using radiotelemetry collars and implants we investigated home range, habitat use and body temperature dynamics of six capybaras (Hydrochoerus hydrochaeris). The study took place in a deforested area of the Central Dry Chaco region of Paraguay recently invaded by the species. Results: The results show that the average home range of capybaras was 183 ha, similar to reported home ranges of capybaras in the Brazilian Pantanal. Within the study area, capybaras used and selected water significantly more than Chaco forest and pasture land, and had lower than expected use of shrub forest. Overall, capybaras were located 95% of the time < 500 m from permanent water, with the greatest distances from water occurring at 3:00 and 5:00 AM. Average year round body temperature was 36.15 Â°C. There was a significant positive correlation between body temperature and distance from water, and a significant negative correlation between distance from water and Chaco ambient temperature. Discussion: These findings suggest that capybaras use water to thermoregulate. The results show how anthropogenic habitat modification has allowed capybaras to thrive in a harsh xeric environment, and assists us in understanding how capybaras can expand into deforested areas. This study provides valuable information for the future management of the species in the Dry Chaco region of Paraguay. Key words: Capybara, Chaco region, habitat use, home range, invasive species, thermoregulation.